Inactivation of Indoor Environmental Allergy-Related Substances by Ozone Gas in a Small Chamber - Yoshinobu Murakami; Yukio Tobi; Kota Emura; Kimiye Baba; Masahiko Taniguchi; Fukumi Furukawa (Trends in Immunotherapy, 2026)
Allergic diseases are increasingly recognized as a worldwide public health problem, affecting countries at all levels of economic growth. In recent years, it has been proposed that allergic diseases result from excessive type 2 inflammation, which is driven by cooperative interactions between the innate and acquired immune systems. In this model, allergens, pathogen-associated molecular patterns (PAMPs), and proteases would all be considered allergen-associated substances. In this study, the Japanese ceder allergen Cry j1 and the house dust mite (HDM) allergen Der f1 were selected as representative allergens; lipoteichoic acid (LTA) from Staphylococcus aureus as a PAMP; and V8 protease (V8) from S. aureus, fungal Alternaria extract (Alt), and HDM fecal extract Dff as proteases. The effects of ozone gas on these substances were investigated in terms of allergenicity, proinflammatory activity via innate immunity, and protease activity. Ozone gas inactivated the allergenicity of both Cry j1 and Der f1, and the protease activities of V8, Alt, and Dff, in a CT value (the product of concentration [C] and exposure time [T])-dependent manner. The proinflammatory activity of LTA via innate immunity was significantly inactivated after ozone exposure (301 ppm·min). Although this study was carried out in a small chamber at the basic research level, the results suggest that ozone gas can inactivate indoor allergy-related substances and may help alleviate allergic symptoms. With appropriate safety measures, such as using it in a closed system, this technology has great potential for practical application to allergy management.